Exploring the factors driving the sustainable consumer intentions for over-the-air updates in electric vehicles - Shanshan Wang; Asif Khan (Energy Exploration & Exploitation)
With the development of intelligent and connected vehicles, over-the-air (OTA) updates empower cars with continuous evolution capabilities, leading to an accelerated penetration rate and steady market share growth. This research endeavors to construct a comprehensive model to understand and predict sustainable consumer intentions to purchase electric vehicles (EVs) and their inclination to pay for OTA updates for EVs. Empirical validation of the model was conducted through partial least squares structural equation modeling (PLS-SEM), using responses from 504 Chinese participants gathered through an online survey. The study demonstrates that instrumental attributes, product innovativeness, and driving experience have indirect effects on the intention to purchase both EVs and OTA updates. This indirect effect is observed through the construct of relationship quality, which includes trust and satisfaction. Moreover, satisfaction and trust are found to have significant and positive associations with purchase intentions for both EVs and OTA updates. This research offers valuable insights for policymakers and marketers seeking to promote EV purchases and OTA updates. It also contributes to the academic implication of intention and behavior in the context of sustainable transportation.